A metabolite attenuates neuroinflammation, synaptic loss and cognitive deficits induced by chronic infection of Toxoplasma gondii - He, Yan; Xu, Daxiang; Yan, Ziyi; Wu, Yongshuai; Zhang, Yongsheng; Tian, Xiaokang; Zhu, Jinhang; Liu, Zhuanzhuan; Cheng, Wanpeng; Zheng, Kuiyang; Yang, Xiaoying; Yu, Yinghua; et al. (Frontiers in Immunology, 2022)
Background Neurodegenerative diseases including AD is currently one of intractable problems globally due to the insufficiency of intervention strategies. Long-term infection of Toxoplasma gondii (T. gondii) can induce cognitive impairment in hosts, which is closely implicated in the pathogenesis of neurodegenerative diseases. Aconitate decarboxylase 1 (Acod1) and its produced metabolite itaconate (termed Acod1/itaconate axis), have recently attracted extensive interests due to its anti-inflammatory role in macrophages. However, whether the axis can influence cognitive function remains unknown. Methods A chronic T. gondii-infected mice (C57BL/6J) model was established via administration of cysts by gavage. Novel location (NL), novel object recognition (NOR), Y-maze spatial memory and nest building tests were used to evaluate the behavior performance. Transmission electron microscopy, immunofluorescence, RT-PCR, western-blotting and RNA sequencing were utilized to determine the pathological changes, neuroinflammation and transcription profile in hippocampus tissues post infection, respectively. Moreover, the protective effect of Acod1/itaconate axis in T. gondii-induced cognitive deficits was evaluated. Results We found that the latent infection of the parasite impaired the cognitive function, which was assessed behaviorally by novel location (NL), novel object recognition (NOR), Y-maze spatial memory and nest building tests. RNA sequencing of hippocampus showed that the infection downregulated the expression of genes related to synaptic plasticity, transmission and cognitive behavior. To our attention, the infection robustly upregulated the expression of genes associated with pro-inflammatory responses, which was characterized by microglia activation and disorder of Acod1/itaconate axis. Interestingly, administration of dimethyl itaconate (DI, an itaconate derivative with cell membrane permeability) could significantly ameliorate the cognitive deficits induced by T. gondii, which was proved by improvement of behavior performance and synaptic ultrastructure impairment, and lower accumulation of pro-inflammatory microglia. Notably, DI administration had a potential therapeutic effect on the cognitive deficits and synaptic impairment induced by the parasitic infection. Conclusions Overall, these findings provide a novel insight for the pathogenesis of T. gondii-related cognitive deficits in hosts, and also provide a novel clue for the potential therapeutic strategies.